Signs and symptoms in Gaucher Disease: priority nursing diagnoses - Márcia Koja Breigeiron; Vitória da Costa Moraes; Janice Carneiro Coelho
ABSTRACT Objective: Identify the signs and symptoms of patients with Gaucher Disease, inferring possible priority nursing diagnoses. Method: Cross-sectional study, developed in a specialized laboratory, between 2013 and 2015. The sample (n = 91) comprised the records of patients with genetic diagnosis for Gaucher Disease. The study respected research norms. Results: Prevalence of female sex (57.1%), age at diagnosis between 0 and 10 years, and origin from the Southeast Region of Brazil were prevalent. Hematologic changes, bone pain, hepatomegaly, splenomegaly, and fatigue were the most recurrent signs and symptoms. The inferred diagnoses for the studied population were: Risk for bleeding; Fatigue; Chronic pain and Acute pain; Impaired physical mobility; Imbalanced nutrition: less than body requirements; and Risk for Developmental Delay. Conclusion: The establishment of Priority Nursing Diagnoses based on signs and symptoms makes it possible to achieve expected outcomes for each individual in the care context.